The Rationality of Intertemporal Choice Model Selection - Feasibility of the Hyperbolic Discounting Theory in the Area of Financial Accounting Measurement - Dongdong Wang, Dongdong; Dongdong Wang, Dongdong Wang; Dongdong Wang, Dongdong Wang; Dongdong Wang, Dongdong Wang (2017)
The widespread application of present value technique in the area of financial accounting measurement, such as fair value measurement, pension plan valuation, impairment loss valuation, has highly improved the fairness and accuracy of accounting information. However, with the development of behavioral economics and many anomalies emerging, the growing criticism of conventional classic economic assumptions has become increasingly obvious, especially after the 2008 financial crisis. This paper mainly focuses on the appropriateness of discount theories and models application and the development direction of present value technique in the area of financial accounting measurement. The whole paper aimed to promote the development process in the field of present value technique, and expected to enhance the accuracy and fairness of accounting information.